[Industrie charbonnière : lettre aux membres de la Chambres des Représentants et du Sénat] - Jottrand, Aug.; Deladrière, G.; Thiébaut, J. (Mons, 1904)
Bibliotheek E. Anseele
Frans
Brochure
Keywords: steenkoolmijnen